Novel Resistant Maltodextrin Alters Gastrointestinal Tolerance Factors, Fecal Characteristics, and Fecal Microbiota in Healthy Adult Humans - Fastinger, Nathaniel D; Karr-Lilienthal, Lisa K; Spears, Julie K; Swanson, Kelly S; Zinn, Krista E; Nava, Gerardo M; Ohkuma, Kazuhiro; Kanahori, Sumiko; Gordon, Dennis T; Fahey, George C. Jr (Journal of the American College of Nutrition, 2008)
OBJECTIVE: Resistant maltodextrin has been shown to increase fecal bulk by resisting digestion and being partially fermented by colonic bacteria to short-chain fatty acids (SCFA). The objective of this experiment was to determine potential prebiotic effects, gastrointestinal tolerance, and fecal characteristics of free-living humans fed a novel resistant maltodextrin or a normal maltodextrin control. METHODS: Subjects (n = 38) were enrolled in a randomized, double-blind study where they were assigned to one of three daily treatments: 15 g maltodextrin; 7.5 g maltodextrin plus 7.5 g resistant maltodextrin (Fibersol-2®; Matsutani Chemical Company, Hyogo, Japan); and 15 g resistant maltodextrin. The experiment lasted 7 wk and consisted of a 2 wk baseline period, a 3 wk treatment period, and a 2 wk washout period. During wk 3 to 5 (treatment period), subjects consumed their assigned treatments. RESULTS: Resistant maltodextrin supplementation tended to increase (p = 0.12) fecal Bifidobacterium populations during the treatment period, altered (p < 0.05) bacterial populations from baseline to treatment, and resulted in very minor effects in gastrointestinal tolerance. There was a shift (p < 0.05) in molar proportions of SCFA towards butyrate, the preferred energy substrate of colonocytes. CONCLUSION: Resistant maltodextrin supplementation was well tolerated, resulted in favorable fermentation characteristics in the large bowel, and also resulted in a change in bacterial populations.